2009
DOI: 10.1007/s11661-009-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of Forming Limit for Rotational Incremental Sheet Forming of Magnesium Alloy Sheet

Abstract: As a lightweight material, magnesium is being increasingly used for automotive parts. However, due to a hexagonal-closed-packed (hcp) crystal structure, in which only the basal plane can move, magnesium alloy sheets exhibit a low ductility and formability at room temperature. Press forming of magnesium alloy sheets is conventionally performed at elevated temperatures of 200°C to 250°C and thus is known as energy consumed forming. Therefore, in view of an energy saving forming technology, we study magnesium all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 36 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…[15][16][17] Kim and Yang [18] proposed a double-forming technique to improve formability, assuming that only shear deformation occurs in the material. Plus, Park et al [19] studied and showed the possibility of cup incremental forming of a magnesium sheet at RT with a rotational tool, where the tool rotates itself.…”
Section: Duc-toan Nguyen Jin-gee Park and Young-suk Kimmentioning
confidence: 99%
See 3 more Smart Citations
“…[15][16][17] Kim and Yang [18] proposed a double-forming technique to improve formability, assuming that only shear deformation occurs in the material. Plus, Park et al [19] studied and showed the possibility of cup incremental forming of a magnesium sheet at RT with a rotational tool, where the tool rotates itself.…”
Section: Duc-toan Nguyen Jin-gee Park and Young-suk Kimmentioning
confidence: 99%
“…Therefore, Park et al [19] proposed rotational incremental sheet forming, which improves the formability of sheet materials, when compared with ISF, due to the large amount of heat generated in the contact area as a result of the friction energy at the tool-specimen interface and plastic deformation energy from the shear deformation.…”
Section: Duc-toan Nguyen Jin-gee Park and Young-suk Kimmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Park et al (2010) used the rotational tool to accelerate plastic deformation of magnesium forming using SPIF. During the rotational incremental forming process, a large amount of heat is naturally generated in the contact area due to friction energy at the tool-specimen interface and plastic deformation energy by shear deformation.…”
Section: Increased Process Capabilitymentioning
confidence: 99%